2007
DOI: 10.1002/art.22664
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 mediates insulin‐like growth factor 1 and interleukin‐1β signaling in an age‐dependent manner in equine articular chondrocytes

Abstract: Objective. Many metabolic processes in chondrocytes thought to contribute to age-related changes in the extracellular matrix are influenced by known roles of Hsp90. Age-related decreases in the level of Hsp90 have been documented in numerous cell types and could contribute to cartilage degeneration. The aim of this study was to investigate the roles of age and Hsp90 in insulin-like growth factor 1 (IGF-1) and interleukin-1␤ (IL-1␤) signaling in chondrocytes.Methods. Levels of Hsp90 messenger RNA (mRNA) and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 48 publications
(49 reference statements)
1
25
2
Order By: Relevance
“…IL-1␤ in particular has been shown to downregulate the expression of insulin receptor substrate-1 and to inhibit Akt phosphorylation (5,17,24,27,45,52). This present study also found a substantial decline in the magnitude of insulin-induced Akt activation in the presence of IL-1␤.…”
Section: Discussionsupporting
confidence: 77%
“…IL-1␤ in particular has been shown to downregulate the expression of insulin receptor substrate-1 and to inhibit Akt phosphorylation (5,17,24,27,45,52). This present study also found a substantial decline in the magnitude of insulin-induced Akt activation in the presence of IL-1␤.…”
Section: Discussionsupporting
confidence: 77%
“…In animal models, Insulin like growth factor-I has led to enhanced repair of extensive cartilage defects and protection of the synovial membrane from chronic inflammation (Fortier & Miller, 2006;Goodrich et al, 2007). However, studies of human articular cartilage indicate that serum Insulin like growth factor-1 levels and chondrocyte responsiveness to Insulin like growth factor-1 diminish progressively with age (Ashton & Matheson, 1979;Boehm et al, 2007;Fortier & Miller, 2006;Loeser et al, 2002;Loeser et al, 2000;Trippel, 1995) This finding suggests that a simultaneous decrease in the amount of Insulin like growth factor-1 available and a reduced ability of cells to respond to the remaining Insulin like growth factor may produce cartilage that is less capable of maintaining its structural and functional integrity. Insulin like growth factor non-responsiveness has been further observed to exist in chondrocytes from arthritic cartilage or in the presence of inflammation (Verschure et al, 1996).…”
Section: Intra-articularmentioning
confidence: 99%
“…Gruber and colleagues found that the addition of IGF-1 increased cell survival upon experimental induction of apoptosis in spine disc annulus fibrosus cells (180), consistent with the anti-catabolic capacity of IGF-1 in both intervertebral disc (IVD) and articular cartilage tissues. Despite its potent anabolic and anti-catabolic effects on normal cartilage tissue, however, IGF-1 appears to have a diminished ability to stimulate ECM formation and decrease catabolism with both age (181,182) and OA (68,149,181). There appears to be an uncoupling of IGF-1 responsiveness in OA, as IGF-1 is able to stimulate matrix synthesis but is unable to decrease matrix catabolism (183).…”
Section: Igf-1mentioning
confidence: 99%